Optimalisasi Manajemen Perubahan dalam Mewujudkan Pembangunan Zona Integritas Menuju Wilayah Bebas Korupsi dan Wilayah Birokrasi Bersih dan Melayani : Studi pada Lapas Kelas IIB Ciamis - Asep Deni Wahyudi; Ading Rahman Sukmara; Enas Enas (International Forum of Researchers and Lecturers, 2024)
Failure in Realizing the Development of the Integrity Zone Towards WBK/WBBM is due to the failure to develop a systematic and consistent change in mindset and work culture. This failure is due to the failure to form an effective work mechanism, the failure to form a mindset of employees in public services, and leaders who have not optimally provided influence as role models. Releasable theories as stipulated in Permenpan RB Number 90 of 2021. The research method uses qualitative descriptive research methods. The results of the study (1) The involvement of all employees is very important because it shows commitment and responsibility in developing the Integrity Zone (2) The aspect of Change Management is collective work and high commitment from employees. (3) Optimization of Change Management includes developing changes in mindset and work culture, in the agenda of change, leadership as a role model has high optimism. (4) Controlling resistance to change requires strategic efforts in handling it.